Nanostructured platform integrated into a microfluidic immunosensor coupled to laser-induced fluorescence for the epithelial cancer biomarker determination - Fernández Baldo, Martín Alejandro (2016)
In the present work, we report a microfluidic immunosensor with a nanostructured platform based in zinc oxide nanoparticles covered by polyvinyl alcohol (ZnONPs-PVA) coupled to laser-induced fluorescence (LIF) for detection of epithelial cell adhesion molecule (EpCAM). EpCAM is a cell surface protein, and is overexpressed by epithelial carcinomas as such as the lung, colorectal, breast, prostate, head, neck, and hepatic origin. The detection limits (LODs) calculated for our method and for a commercial enzyme-linked immunosorbent assay (ELISA) test kit were 1.2 and 13.9 pg mL-1, respectively. The within- and between-assay variation coefficients for the proposed method were below 6.50%. The results correlated well with those obtained with the commercial ELISA method, thus demonstrating that the new nano-platform integrated into a microfluidic device offers a truthful and useful analytical tool to be easily applied in epithelial cancer diagnosis through EpCAM biomarker determination.